2013
DOI: 10.4028/www.scientific.net/amm.405-408.2089
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes of Water Discharge and Sediment Load in the Buyuan River Basin, China

Abstract: Changes in stream flow and sediment load in the Buyuan River Basin is a focus due to its vital ecological niche in supply feeding and spawning habitats for upstream migrant fish species of Mekong River. Based on the precipitation and water discharge series data (19592008), and sediment load series data (19932008), the runoff and sediment discharge variation and its response to precipitation has been analyzed. The results shown that, during the study period of 19592008 at the Manan gauging station, annual runof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The Buyuan River, located between 21°40 N–23°08 N and 100°52 E–101°40 E, spans the cities of Pu'er and Xishuangbanna in Yunnan Province and has a total length of 370 km, while the total catchment area of the basin is 7679 km 2 (Zhong et al, 2013). The climate of the BRB can be classified as subtropical monsoon with an average annual temperature and precipitation of 21.5°C and 1488 mm, respectively, with the rainy season extending from June to November.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Buyuan River, located between 21°40 N–23°08 N and 100°52 E–101°40 E, spans the cities of Pu'er and Xishuangbanna in Yunnan Province and has a total length of 370 km, while the total catchment area of the basin is 7679 km 2 (Zhong et al, 2013). The climate of the BRB can be classified as subtropical monsoon with an average annual temperature and precipitation of 21.5°C and 1488 mm, respectively, with the rainy season extending from June to November.…”
Section: Study Areamentioning
confidence: 99%
“…Several studies have analyzed the runoff variation trend of the BRB in the past decades. The majority of these studies focused on the temporal and spatial distribution of the runoff and the potential impacts of changes in the runoff (Bi, Zhao, Xiao, Zhou, & Zhang, 2015; Jiang, Wang, Shen, Lu, & Ni, 2019; Liu, Liu, Lu, Duan, & Li, 2011; Yu, Pan, Liu, Chen, & He, 2017; Zhong, He, & Fu, 2013). Most of these studies used statistical methods to analyze the observed data, which directly reflect the changes in hydrological factors, but it is difficult to analyze the impact of future climate change on the runoff.…”
Section: Introductionmentioning
confidence: 99%